Orthodox versus heterodox (Minskyan) perspectivesof financial crises: Explosion in the 1990s versus implosion in the 2000s - Jesús Mu\~noz (Levy Economics Institute of Bard College, 2011)
Orthodox and heterodox theories of financial crises are hereby compared from a theoretical viewpoint, with emphasis on their genesis. The former view (represented by the fourthgeneration models of Paul Krugman) reflects the neoclassical vision whereby turbulence is an exception; the latter insight (represented by the theories of Hyman P. Minsky) validates and extends John Maynard Keynes's vision, since it is related to a modern financial world. The result of this theoretical exercise is that Minsky's vision represents a superior explanation of financial crises and current events in financial systems because it considers the causes of financial crises as endogenous to the system. Crucial facts in relevant financial crises are mentioned in section 1, as an introduction; the orthodox models of financial crises are described in section 2; the heterodox models of financial crises are outlined in section 3; the main similarities and differences between orthodox and heterodox models of financial crises are identified in section 4; and conclusions based on the information provided by the previous section are outlined in section 5. References are listed at the end of the paper.
Keywords: B00; B20; B30; B50; E0; E12; E13; E60; F0; F3; F4; 330; John Maynard Keynes; Hyman P. Minsky; Paul Krugman; financial crises; financial fragility; asset bubbles; speculation